ChemInform Abstract: Conversion of Azides into Diazo Compounds in Water. Issue 11 (18th March 2014) - Chou, Ho‐Hsuan; Raines, Ronald T.
Abstract A new phosphinoester mediates the conversion of azides into diazo compounds in phosphate buffer at pH 7.0.